Underwater Technology Research Group (UTeRG) Glider for Monitoring and Surveillances Applications - Mohd Aras, Mohd Shahrieel; Abdul Azis, Fadilah; Fara Ashikin , Ali; Arfah Syahida, Mohd Nor; Lim , Wee Teck (2011)
This paper describes a design and development of Underwater Glider for Monitoring and surveillances applications. An Underwater Glider is a type of Autonomous Underwater Vehicle (AUV). Underwater gliders are buoyancy-driven device. It can alternately reduce and expand displaced volume to dive or climb through the ocean. It has wings to control its motion from vertical to horizontal at very low power consumption. The motivation of this underwater glider is at its long range and high endurance for certain types of mission. Gliders are designed to slip through the ocean a fraction of meter per second to cover hundreds of meters for weeks. It can be used in commercial and military purpose. The design and development of this underwater glider have hydrodynamic characteristic, stability and buoyancy. The simple Microprocessor PIC is used to control the movement of the glider. There are three major phase in developing this glider which are mechanical design, programming and fabrication. The speed and power consumption of the glider in pool and lake are then measured and analyzed. This glider was tested on three types of differences testing area such as lake, swimming pool and laboratory pool. This paper also shows the performances of glider in term of speed and power consumption of three conditions. This glider is proven suitable for monitoring and surveillances application.